Executive Functioning in Children with Congenital Adrenal Hyperplasia. (January 2017) - Agoston, A Monica; Gonzalez-Bolanos, Maria Teresa; Semrud-Clikeman, Margaret; Vanderburg, Nancy; Sarafoglou, Kyriakie
Congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency is a disorder characterized by impaired cortisol synthesis leading to excessive production of adrenal androgens. Prenatal and postnatal exposure to excess androgens may increase neural vulnerability to insult and affect cognitive functions, particularly dopamine-dependent neural circuits responsible for executive functioning (EF). Our study aimed to investigate relationship between more pronounced androgen exposure and EF-related behaviors in children with CAH, as well as sex differences in these associations. Parents of patients with CAH (n=41, boys=17, girls=24; age: M=8.41, SD=4.43) completed the Behavior Rating Inventory of Executive Function (BRIEF), a measure assessing behavioral manifestations of EF. Assessments of bone age advancement, a proxy of cumulative androgen exposure, were analyzed. Advanced bone age predicted more inhibition difficulties in boys but not in girls, and more difficulties in all other BRIEF domains in the total sample. Excessive androgen production affected EF such that more advanced bone age led to more EF-related difficulties. Sex differences in inhibition may result from estrogen exposure moderating the impact of androgens in girls but not in boys. Future interventions may include targeting EF in patients with CAH to enhance quality of life and reduce cognitive consequences associated with this disease.